Biosynthesis Of Gold Nanoparticles With Four Different Lactobacillus Species - Sara Bahram Miran; Fattma Abodi Ali (Eurasian Journal of Science and Engineering, 2023)
Exopolysaccharide production by many lactic acid bacteria of diverse genera and species has been widely explored. In this study, the biosynthesis of gold nanoparticles using cell-free culture supernatant of bacterial species was explored. A total of 500 saliva samples were obtained from the oral cavity, then the samples were cultured and examined. The 500 saliva samples contained 19 oral bacteria, which included Lactobacillus fermentum, Lactobacillus plantarum, Lactobacillus casei, and Lactobacillus paracasei, that extracellularly produced gold nanoparticles when exposed to chloroauric acid (HAuCl4). Biosynthesis of gold nanoparticles made by reducing HAuCl4 using the cell-free culture supernatant of the four different species of Lactobacillus. Characterizations of the gold nanoparticles were identified by Ultraviolet-Visible Spectroscopy, Fourier Transform Infrared Spectroscopy, Particle Size Analyzer (Dynamic Light Scattering), Zeta Potential, X-Ray Powder Diffraction, Transmission Electron Microscopy, Energy Dispersive X-Ray Analysis, and Atomic Force Microscopy. Given that Lactobacillus species are engaged in the formation of gold nanoparticles, this method may be more useful than chemical and physical methods, as it is cost-effective and eco-friendly.